EVALUATING THE TRANSPORT SYSTEM EFFICIENCY OF PUMPING ELECTRICALLY CONDUCTIVE LIQUID BASED ON THE RESULTS OF MATHEMATICAL MODELING - Chernetskaya-Beletskaya, N. B.; Rogovyi, A. S.; Miroshnykova, M. V. (Systems and Technologies, 2021)
Today in many industries there is a need to pump electrically conductive fluids. In contrast to classical hydrodynamics, MHD modeling requires the simultaneous solution of the equations of hydrodynamics and electrodynamics, which significantly complicates the modeling process. For electrically conductive fluids, such a number of experimental studies has not yet been conducted, in addition, the dependencies are complicated by the influence of the magnetic field and the need to take into account their magnitude. An urgent task is to determine the dependences of the pressure losses of local resistances during the flow of electromagnetic fluids on electromagnetic and hydrodynamic parameters. The development of computational hydrodynamics in recent years has led to the fact that the use of CFD-calculations can practically replace valuable experimental studies of electrically conductive fluids by mathematical modeling. Experimental studies are complicated by the use of powerful electromagnets and a variety of electrically conductive fluids, which often have not only electromagnetic properties, but are often non-Newtonian. Based on the numerical simulation of the flow of conductive fluid in the pipeline elbow, the dependences of the pressure losses at the bend in the elbow were determined by solving the Navier – Stokes equations averaged according to Reynolds. The magnetic field has a significant effect on the diagram of the velocity before and after the turn in the knee due to the fact that the magnetic induction vector in either the first or second section is perpendicular to the tube. At relatively small values of Reynolds numbers, the effect of the magnetic field is very significant, which increases the local resistance coefficient by more than 15 times compared to the coefficient without the action of the magnetic field.